The Impact of Chinese Banking Management on the Loan Loss Provision - Zhang, Miao (2017)
This dissertation mainly studies the behavior of the managers in Chinese banking industry about the loan loss provisions (LLPs) of the banks during the time from 2011 to 2016. By using the model we mainly consider the influence of capital management, income smoothing and cyclical management on the behavior of LLP, we also introduce the variable of X-efficiency score to test the relationship between it and LLP. X-efficiency may bring new possibility to the whole estimation model.